2018
DOI: 10.1186/s12889-018-5035-3
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol marketing on YouTube: exploratory analysis of content adaptation to enhance user engagement in different national contexts

Abstract: BackgroundWe know little about how social media alcohol marketing is utilized for alcohol promotion in different national contexts. There does not appear to be any academic work on online exposure to alcohol marketing via social media in India, and most of the limited research in Australia has focused on Facebook. Hence, the present study extends previous research by investigating alcohol promotion conducted on an under-researched form of social media (YouTube) in two contrasting geographic contexts. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…However, YouTube's marketing communication impact can also be assessed via a variety of cues, such as advertisement recall, engagement, understanding and feedback [32], and/or through consumer reviews, which express sentiment towards marketing communication and have influence on the audience's future purchase behaviour. However, a majority of academic inquiries assess YouTube marketing communication effectiveness via qualitative in-depth interviews [34,37,62], content analysis [7,14,21,36], and/or attitudinal surveys [15,16,19,20,22,23,26,28,29,35,[39][40][41][42][43][44]63]. This study has adopted the latter approach, using a cross-sectional approach to assess Millennials' affective A ad responses regarding YouTube marketing communication.…”
Section: Youtube and Marketing Communicationmentioning
confidence: 99%
“…However, YouTube's marketing communication impact can also be assessed via a variety of cues, such as advertisement recall, engagement, understanding and feedback [32], and/or through consumer reviews, which express sentiment towards marketing communication and have influence on the audience's future purchase behaviour. However, a majority of academic inquiries assess YouTube marketing communication effectiveness via qualitative in-depth interviews [34,37,62], content analysis [7,14,21,36], and/or attitudinal surveys [15,16,19,20,22,23,26,28,29,35,[39][40][41][42][43][44]63]. This study has adopted the latter approach, using a cross-sectional approach to assess Millennials' affective A ad responses regarding YouTube marketing communication.…”
Section: Youtube and Marketing Communicationmentioning
confidence: 99%
“…As stated earlier, alcohol companies use marketing strategies on SNS that are tailored to specific national contexts and users’ responses to such marketing content differ by national settings [ 22 – 24 ]. These studies identified common strategies used for alcohol promotion across social media in both countries.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies related to the use of social media are; 1) How social media alcohol marketing is utilized for alcohol promotion in different national contexts (India and Australia) [10]. 2) Undergraduate music education students created music videos during an informal music learning project in an introduction to music education and technology courses at a large, Midwestern, public university [11].…”
Section: Methodsmentioning
confidence: 99%